Tiempo de chicas : identidad, cultura y poder - Elizalde, Silvia (Juventudes argentinas hoy., 2015)
Unlike their mothers, young women today enjoy a battery of rights and opportunities unthinkable just a few decades ago. They are, at the same time, protagonists of a new public visibility that, while placing them on the podium of beauty, fashion and entertainment as the epitome of success and fetish of male desire, stimulates them to continue and deepen their struggles. opened by their predecessors for the demand for equity. In any case, their emerging feminities confront institutions, parents and adults in general with numerous questions about the cultural and political implications of a virtual new gender order among youth. Focusing on different testimonies and experiences of girls from the middle and popular sectors about their interactions with the media, the cultural industry, the market, public policies and art, this book attempts to problematize the current social status of young women . Because it is, without a doubt, girl time: of their actions, their voices and their assemblages. And because listening to them today is both a challenge and a stinging question.